Examination of the potential anticancer activities and moleculer mechanics of drimia calcarata buld exctracts against different cancer cells - Laka, Kagiso (My University, 2023)
Cancer remains uncurable, and the current treatment strategies are associated with inefficiency and adverse side effects. The majority of the populace relies on traditional doctors who prescribe medicinal plants to treat a plethora of ailments. Even with the existence of modern medicine, traditional medicines have sustained their therapeutic popularity for cultural and historical reasons. Natural products such as earthly plants are said to have directly or indirectly contributed to 74% of therapeutic drugs developed today, and have served as a platform from which novel therapies could be developed. Drimia calcarata (D. calcarata) is one of the plants used by Pedi people to treat a plethora of ailments; however, the anticancer therapeutic use of D. calcarata is less understood. The anticancer potential of this plant has been reported from cell viability study, but there is little information on its anticancer molecular mechanisms; thus, the aim of this study was to investigate the potential anticancer activities and molecular mechanisms of D. calcarata bulb extracts against different human cancer cells. The phytochemicals of the D. calcarata bulb extracts were analysed using the Thin Layer Chromatography (TLC), qualitative phytochemical tests, and Liquid Chromatography Mass Spectrometry (LC-MS), while the antioxidant activity of the plant was investigated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and Ferric Reducing Antioxidnt Power (FRAP) assays. The Total Phenolic content (TPC), Total Tannin (TTC) and Total Flavonoid Content (TFC) were also determined. The inhibitory effects and half maximal inhibitory concentration (IC50) values of D. calcarata extracts were determined using the MTT and Muse® Count and Viability assays. Induction of cellular apoptosis was assessed using fluorescence microscopy, the Muse® Cell Analyser, and gene expression analysis by Polymerase Chain Reaction (PCR).The proteins expressions were analysed using Immunocytochemistry (ICC), Western blotting analysis and Proteome protein Profiler Arrays. This study demonstrated that the Drimia calcarata bulb water and methanol extracts possessed significant amounts of tannins and flavonoids with antioxidant activities. Using LC-MS, several phytochemicals were identified in D. calcarata bulb extracts, with most implicated in anticancer activities. Psoralene was identified as the major compound in D. calcarata water and methanol fractions, which can be attributed to the antioxidant activity observed from the D. calcarata bulb water and methanol extracts. These suggest that D. calcarata plant contain healthy and beneficial phytochemicals that can be targeted for disease prevention and drug development, especially against different cancers. In this study, the anticancer activities of the D. calcarata bulb extracts were investigated against different human cancer cell lines. Both the methanol and water extracts demonstrated safety against non-canceruous HEK-293 cells and selective anticancer activities against colorectal cancer cells. The methanol extract inhibited the growth of colorectal Caco-2 cancer cells; however, the same cells showed resistance against the water extract. On the other hand, the colorectal HT-29 cancer cells showed sensitivity to both extracts (P˂0.001). The D. calcarata methanol extract significantly (P˂0.001) induced cell death through an intrinsic p53-dependent apoptotic pathway in both cell lines, while the water extract induced the extrinsic apoptosis pathway in HT-29 cells. The methanol extract upregulated TP53 and downregulated BCL-2, STAT1, STAT3, and STAT5B in HT-29 cells. Additionally, the methanol extract induced caspase-dependent apoptosis. The anticancer effect of the D. calcarata extracts were not only limited to colorectal cancer but other cancer cells, including cervical cancer. The D. calcarata ME and WE showed safety against non-cancerous KMST-6 cells after treatment with the concentrations 62.50-1000 μg/mL. The extracts exhibited anticancer activity against HeLa, with no significant cytotoxic effect against the Ca-Ski cells. The WE increased the Ki67 positive Ca-Ski population, while both ME and WE arrested HeLa cells at G2/M phase, and Ca-Ski cells in G0/G1 phase. AO/EB staining, Annexin V and Caspase 3/7 Activation revealed that the extracts significantly (P˂0.001) induced apoptosis in HeLa cells. In HeLa cells, the ME downregulated TP53 variants, while WE upregulated both TP53 variants in HeLa cells. Additionally, both extracts decreased the STAT5A and STAT5B mRNA expression in HeLa cells; however, these extracts upregulated cancer-promoting STAT3 in Ca-Ski cells. Moreover, these extracts inactivated the PI3K signaling pathway in HeLa cells but not in Ca-Ski cells. The resistance of the Ca-Ski cells to the D. calcarata extracts may be due to the upregulation of STAT3 and persistent activated PI3K signaling pathway. The cytotoxicity and apoptosis induction in HeLa cells by D. calcarata extracts may be attributed due to downregulation of STAT5A survival mechanisms. D. calcarata extracts also displayed antineoplastic effects against T47D and MDA-MB31 breast cancer cells (P˂0.001); however, T47D cell line showed higher sensitivity to the methanol extract. Fluorescence microscopy and Annexin V showed that both extracts induced apoptosis in breast cancer cells; but ME significantly induced a caspase-dependent apoptosis in T47D cells, while the WE significantly (P˂0.001) induced a caspase-dependent apoptosis in MDA-MB-231 cells. RT-PCR showed that the D. calcarata extracts induced p53-dependent apoptosis where the ME upregulated TP53 splice variant 1 and down-regulated splice variant 2 while the WE had an opposite effect on the TP53 splice variants. Additionally, the D. calcarata methanol extracts downregulated BCL2. The Drimia calcarata extracts upregulated the expression of STAT3 and downregulated the expression of STAT5A in both breast cancer cell lines. Treatment of the MDA-MB 231 resulted in downregulation of CLB, cIAP1 and cIAP2 proteins. Interestingly, Caspase-8, p53, β-TrCP1 and FBXO15 protein expressions were upregulated by ME and Curcumin. The data suggest that D. calcarata extracts do not target STAT3-related pathway. Importantly, D. calcarata extracts effectively induced growth inhibition and p53-related apoptosis in human breast cancer T47D and MDA-MB-231 cells through STAT5A regulation. Moreover, the present study indicates that D. calcarata extracts exhibited their anticancer activities against breast cancer MDA-MB-231 cancer cells through the suppression of cIAP1, cIAP2, TNF-R1 proteins while ME and Curcumin also supported the expression of tumour suppressor proteins, FBXW7 and p53, which are known for their anticancer activities. The extracts further demonstrated safety against non-cancerous lung MRC-5 fibroblasts and exhibited significant (P˂0.001) anticancer potency against the H1437 (IC50 values: 62.50 μg/mL ME and 125 μg/mL WE), H1573 (IC50 value: 125 μg/mL for both extracts) and A549 (IC50 value: 500 μg/mL ME). The water extract had no effect on the cell viability of A549 cells. Treated H1437 cells underwent p53-dependent apoptosis and S-phase cell cycle arrest while H1573 treated cells underwent p53-independed apoptosis and G0/G1 cell cycle arrest through upregulation of CDKN1A mRNA expression levels. The expression levels of STAT1, STAT3, STAT5A and STAT5B genes increased significantly following the treatment of H1573 cells with ME and WE. Treatment of H1437 cells with ME upregulated the STAT1, STAT3, STAT5A and STAT5B mRNAs. The results indicate that the proliferative inhibitory effect of D. calcarata extracts on A549 and H1573 cells is correlated with the suppression of BCL2, STAT3 and STAT5B while that is not the case in H1437 cells. Thus, these results suggest that the dysregulation of anti-apoptotic molecules, BCL2, STAT3, STAT5A and STAT5B, in H1437 may play a role in cancer cell survival, which may consequently contribute to the development of TP53-mutated non-small human lung cancer. The growth inhibition of human lung cancer cells by D. calcarata extracts was also observed and was found to be associated with induction of apoptosis and G0/G1 and S-phase cell cycle arrest. D. calcarata anticancer activities against lung cancer cells was attributed to the activation of TP53 tumour suppressor gene, and inhibition of the anti-apoptotic gene, BCL-2, and cancer-related gene, RBBP6, which has been implicated in both cell cycle and apoptosis regulation. All the anticancer activities that were deciphered in different cell lines can be attributed to anticancer compounds that were detected in D. calcarata bulb extracts. Scillaren A, Protocatechuic acid, Vanillic acid, Chlorogenic acid and Limonin showed safety against the non-cancerous HEK-293 cells. Scillaren A showed potent activity against the HeLa and T47D cancer cells. Furthermore, the study has shown that Protocatechuic acid, Vanillic acid, Chlorogenic acid and Limonin exhibited selective cytotoxicity against Ca-Ski, MDA-MB-231 and T47D. Therefore, D. calcarata extracts and its constituents could be useful for therapeutic use against various human cancer cells. Further studies are required to determine the identity and biological functions of the unknown compounds that were detected in methanol and water D. calcarata bulb extracts. In vivo studies should be considered, post this study, to study novel formulations derived from Drimia calcarata phytochemicals. Taking into account all these suggestions will help in identifying novel compounds with less to no side effects.
Thesis (Ph.D. (Biochemistry)) -- University of Limpopo, 2023
Keywords: Protocatechuic acid; Potential anticancer; Molecular mechanisms; Drimia calcarata; Cancer cells; Blood cells; Antineoplastic agents; Cancer -- Treatment; Traditional medicine; Cancer cells